2001
DOI: 10.1590/s0037-86822001000300006
|View full text |Cite
|
Sign up to set email alerts
|

Formas graves de leptospirose: aspectos clínicos, demográficos e ambientais

Abstract: Abstract Abstract Abstract Characteristics of 1,016 patients hospitalized with leptospirosis in the Hospital Couto Maia, Salvador, BA, Brazil, between 1993 and 1997 are described. Higher pluviometric precipitation was related to an increase in the number of hospitalizations during the following month. Males corresponded to 81.1% (824/1,016) of these; mean age was 35.7±15.4 years. Almost 94% (778/829) of the 829 patients with information about race were black or mulatto (mixed race). For ages 18 years or above,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
10
0
9

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 18 publications
3
10
0
9
Order By: Relevance
“…The results from the present study were concordant with data from other investigations, such as the studies by Costa et al 9 and Romero et al 15 These authors concluded that the disease was associated with low socioeconomic level, with increases in the numbers of cases with increasing rainfall. cases were predominantly registered in regions without adequate sanitary infrastructure, urban development condition and garbage collection, and that populations without sewage treatment, living beside rivers that were liable to fl ood, were more exposed to infection by Leptospira.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The results from the present study were concordant with data from other investigations, such as the studies by Costa et al 9 and Romero et al 15 These authors concluded that the disease was associated with low socioeconomic level, with increases in the numbers of cases with increasing rainfall. cases were predominantly registered in regions without adequate sanitary infrastructure, urban development condition and garbage collection, and that populations without sewage treatment, living beside rivers that were liable to fl ood, were more exposed to infection by Leptospira.…”
Section: Discussionsupporting
confidence: 93%
“…Young male adults were the group most contaminated by the disease, as also seen in other studies. 5,9,10,12,15 This was perhaps because they were the ones responsible for rescuing possible victims in cases of fl ooding and landslides caused by rain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salvador is the third most populated city in Brazil, with an estimated 2.6 million inhabitants, and 60% of those inhabitants live in slum communities (Riley et al 2007). It is a large urban center with poor sanitation, and incidence of severe leptospirosis cases peak during rainy seasons and in association with floods (Ko et al 1999, Costa et al 2001, Riley et al 2007. Reports from the Zoological personnel indicated that there is a high population of rodents in the park, and rodents are frequently observed to be in contact with the animals in their cages.…”
Section: Resultsmentioning
confidence: 99%
“…The low frequency of seropositive animals in this study may be justified by the difference in canine populations studied and the lower rainfall observed in the period and region studied. According to Costa et al (2001), an increase in leptospirosis cases occurs with an increase of rainfall.…”
Section: Resultsmentioning
confidence: 99%